Coautorías legislativas y la firma del Acuerdo de Paz en Colombia (2014-2018) (2020)
This research analyzes the professional relationships between Colombian congressmen that influence the creation of coalitions for the presentation of bills. Determining the context variables that explain these coalitions in the last legislative four-year period (2014-2018), this work studies the socio-political characteristics of each actor that determine the legislative work of the congressmen before and after the signing of the Peace Agreement in November of 2016. Based on a centrality analysis, it is concluded that after the signing of the Peace Accords, congressmen present more bills co-authored by members of the same family of parties (government and opposition parties). Before this event, the study shows that the congressmen co-authored among themselves without distinction of party family. Likewise, it is observed that the congressmen members of the permanent constitutional commission present greater centrality than those belonging to other commissions.